2021
DOI: 10.3390/jmse9050544
|View full text |Cite
|
Sign up to set email alerts
|

Study of Microplastics and Inorganic Contaminants in Mussels from the Montenegrin Coast, Adriatic Sea

Abstract: Mussels (Mytilus galloprovincialis) collected at three locations in Boka Kotorska Bay, on the Montenegrin Adriatic coast, were analyzed for the first time by optical and Raman microscopy to detect microplastics (MPs) and other emerging contaminants in their soft tissues. Concentrations of six trace metals (Cu, Zn, Mn, Fe, Cd, and Hg) were also measured in the same samples by atomic absorption spectroscopy. Mussels from a location near the urban area of Kotor were found to exhibit the highest content of MPs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…According to a different study published by [29], fibre made up the majority of all analysed samples of wild organisms, with surf clams and razor clams accounting for 80% of the sample's total MPs. Meanwhile, a research for the IOP Publishing doi:10.1088/1755-1315/1121/1/012008 6 Northern and Central Adriatic claimed that all of the examined samples of the mussel species Mytilus galloprovincialis had nylon threads [30]. Based on a comparison of the results, [30] hypothesised that nylon filaments might function as vectors for the entry of trace metals into mussels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a different study published by [29], fibre made up the majority of all analysed samples of wild organisms, with surf clams and razor clams accounting for 80% of the sample's total MPs. Meanwhile, a research for the IOP Publishing doi:10.1088/1755-1315/1121/1/012008 6 Northern and Central Adriatic claimed that all of the examined samples of the mussel species Mytilus galloprovincialis had nylon threads [30]. Based on a comparison of the results, [30] hypothesised that nylon filaments might function as vectors for the entry of trace metals into mussels.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a research for the IOP Publishing doi:10.1088/1755-1315/1121/1/012008 6 Northern and Central Adriatic claimed that all of the examined samples of the mussel species Mytilus galloprovincialis had nylon threads [30]. Based on a comparison of the results, [30] hypothesised that nylon filaments might function as vectors for the entry of trace metals into mussels. The abundance of MPs in wild mussels, particularly fibres also reported in findings by [31].…”
Section: Resultsmentioning
confidence: 99%
“…Grkovic et al (2021) studied the concentration of toxic elements in mussels aquacultured in Montenegro and revealed that moderate quantities of mussels from the examined area should be safe for consumption. Perošević-Bajčeta et al ( 2021) corroborated that for Boka Kotorska Bay, average concentrations of most elements have decreased over time, but the results of De Simone et al (2021) showed that mussels from the location nearest to a dense urban settlement were characterised by the highest content of pollutants (microplastics, textile fibres, titanium dioxide microparticles) originating from anthropogenic sources. On the contrary, in farmed mussels from the locations with probably higher phytoplankton abundance, higher carotenoid content was found.…”
Section: O N L I N E F I R S Tmentioning
confidence: 97%
“…In the present work, the hemolymphatic cells of the bivalve mollusk Mytilus galloprovincialis were used as model target cells and were in vitro exposed to label-free NPs and, for comparison, to Nile-red-labeled NPs for a time span of 6 h. Bivalve mollusks are widely utilized as bioindicator organisms in coastal and marine biomonitoring and assessment [56,57]. Their high water filtration rate due to their filter-feeding nature makes these organisms particularly vulnerable to the exposure to micro/nanoplastics [58][59][60]. Recent literature reports that polyethylene terephthalate (PET) is one of the most common polymers in Mytilus galloprovincialis in the Adriatic Sea [61,62].…”
Section: In Vitro Exposure Of Mytilus Galloprovincialis Hemolymphatic...mentioning
confidence: 99%